Through their eyes: Israeli-Arab students speak up through participatory documentary photography projects. (July 2018) - Hayik, Rawia
'PhotoVoice' is a participatory documentary photography tool that empowers youth with little money, power, or status by providing them with opportunities to voice their critique and act for enhancing their realities. Grounded in critical literacy theory, this research tool has the potential to raise students' awareness to problematic issues in their surroundings and enable them to highlight such issues to the wider community. This article describes the journey I embarked upon as a teacher-researcher with my college students to apply such a tool in the Israeli-Arab classroom. After engaging a group of third year future English teachers in PhotoVoice projects, students' PhotoVoices were collected and analysed to explore what issues students addressed and the ways they used to do so. A description of the topics that students chose to highlight and the language used for demanding change is followed by students' as well as my reflections on the process.